Unstable solar lentigo: A defined separate entity. (2nd February 2016) - Byrom, Lisa; Barksdale, Sarah; Weedon, David; Muir, Jim
Abstract: An unstable solar lentigo is a solar lentigo with areas of melanocytic hyperplasia not extending past the margin of the lesion. They are discrete, macular, pigmented lesions arising on sun‐damaged skin and a subset of typical solar lentigos. Clinically they differ from usual solar lentigines in often being solitary or larger and darker than adjacent solar lentigines. These lesions are of clinical importance as they can arise in close proximity to lentigo maligna and in a single lesion there can be demonstrated changes of solar lentigo, unstable solar lentigo and lentigo maligna. These observations led us to conjecture that unstable solar lentigos could be a precursor lesion to lentigo maligna. In this article we examine the possibility that lentigo maligna can arise within a solar lentigo through an intermediate lesion, the unstable solar lentigo. We propose that the histopathological recognition of this entity will allow for future research into its behaviour and thus management. We review difficulties in the diagnosis of single cell predominant melanocytic proliferations and the concept of unstable lentigo in view of the literature and clinical experience supporting the proposal of its recognition as a separate entity.